2022
DOI: 10.7150/thno.71086
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis in inflammatory diseases and cancer

Abstract: Pyroptosis is a lytic and inflammatory type of programmed cell death that is usually triggered by inflammasomes and executed by gasdermin proteins. The main characteristics of pyroptosis are cell swelling, membrane perforation, and the release of cell contents. In normal physiology, pyroptosis plays a critical role in host defense against pathogen infection. However, excessive pyroptosis may cause immoderate and continuous inflammatory responses that involves in the occurrence of inflammatory diseases. Attract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(103 citation statements)
references
References 125 publications
(145 reference statements)
0
79
0
1
Order By: Relevance
“…e mechanism of cell death varies. Apoptosis [18], pyroptosis [19], necrosis [20], and ferroptosis [21][22][23] are the most commonly observed. Recently, Tsvetkov et al found a copper-based mechanism that was completely different from the known mechanisms of cell death, and they named it "cuproptosis" [7].…”
Section: Discussionmentioning
confidence: 99%
“…e mechanism of cell death varies. Apoptosis [18], pyroptosis [19], necrosis [20], and ferroptosis [21][22][23] are the most commonly observed. Recently, Tsvetkov et al found a copper-based mechanism that was completely different from the known mechanisms of cell death, and they named it "cuproptosis" [7].…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis refers to programmed cell death triggered by the inflammasomes and executed by gasdermin proteins. The main characteristics of pyroptosis include cell swelling, membrane perforation and the release of cellular contents ( Rao et al, 2022 ). The classical pyroptosis pathway is mediated by the NLRP3/caspase-1/GSDMD pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis, as a new type of programmed cell necrosis, is mainly triggered by inflammasome and releases the intracellular inflammatory factors, and exerts tumor suppression function and evokes anti-tumor immunity responses (17,21,22). To further clarify the role of GALNT6 in PDAC, the effect of GALNT6 on PDAC pyroptosis was investigated.…”
Section: Galnt6 Promotes Inflammation and Pyroptosismentioning
confidence: 99%